Performance of U.S. and German banks under Basel III : how have the new capital and leverage requirements impacted their profitability? - Sá, Guilherme José Ferreira de (2020)
The present Dissertation’s research question addresses the assessment of the new capital and leverage requirements introduced by the Basel III framework. The formulation of the research question focuses on the dynamics of Tier 1 Capital, Tier 2 Capital, and the Leverage Ratio, and their impacts on the profitability and performance of U.S. and German banks. The document’s empirical research design employs a panel data econometric approach for the period between 2009 to 2018. The two-way method based on both fixed and random effects models assesses the reaction of four dependent variables (Return on Equity, Return on Assets, Net Interest Margin, and Efficiency Ratio) on a set of independent variables. Banking data were extracted from The Bloomberg Terminal. This said empirical methodology provides relevant baseline findings regarding the underlying research question. This research’s main findings suggest that the variables included in the model generally negatively impact the profitability of the banks included in the study. The most significant variables in this research are Tier 2 Capital and Leverage Ratio that impact the dependent variables with a 1% significance level. It is hoped that the conclusions might contribute to a better understanding of the application of regulatory reforms and the impacts on the important banking industries of these advanced economies in a post-crisis environment.